Gambling among adolescents and emerging adults: a cross-cultural study between Portuguese and English youth - Calado, C. (2018)
In spite of age prohibitions, most research suggests that a large proportion of adolescents engage in gambling, with problem gambling prevalence rates significantly higher than in adults. There is some evidence suggesting that there are cultural variables that might explain the development of gambling behaviours in this age group. However, cross-cultural studies on this field are generally lacking. The present study tested a model in which individual and family variables are integrated into a single perspective as predictors of youth gambling behaviour in two different contexts (i.e. Portugal and England). A total of 1137 adolescents and young adults (552 Portuguese and 585 English) were surveyed with items relating to problem gambling, gambling frequency, sensation seeking, parental attachment, and cognitive distortions. Moreover, this study is the first to examine the mediation effect of sensation seeking between attachment and youth problem gambling. Results demonstrated that English youth showed a higher prevalence of problem gambling. The findings of this study also demonstrated that sensation seeking was a common predictor, mediating the relationship between attachment and problem gambling in both countries. The findings of this study suggest that although there were some common factors between the two samples, youth problem gambling and some risk factors can be influenced by the cultural context.